The Influence of Financial Ratios, GCG, and Sales Growth on Financial Distress - Salsa Bila, Ghina; Putra Ananto, Rangga; Gustati, Gustati (Jurnal Riset Akuntansi Terpadu, 2024)
The purpose of this study is to investigate how financial distress is impacted by profitability, leverage, institutional ownership, the board of directors, the audit committee, the independent board of commissioners, and sales growth. Secondary data from the 2021–2023 financial statements of companies in the energy and basic material sectors listed on the Indonesia Stock Exchange were used in this study. Purposive sampling was the method utilized, and 72 data were collected based on the study's criteria. Multiple linear regression analysis is done with the SPSS (Statistical Product and Service Solution) version 25 program. Z-SCORE serves as a proxy for the dependent variable financial distress, and the Kolmogorov-Smirnov test, which employs a single sample, demonstrates that it is normally distributed. The study's findings suggest that financial difficulty is influenced by a number of factors, including audit committees, independent boards of commissioners, sales growth, leverage (debt to equity ratio), and profitability (return on assets). Financial distress is unaffected by the board of directors or institutional ownership. Financial distress is simultaneously influenced by sales growth, profitability, leverage, institutional ownership, the board of directors, the audit committee, and the independent board of commissioners.